SHAKESPEARE’S SISTER AND THE CRISIS OF WOMEN’S AUTONOMY: A CRITICAL ANALYSIS OF ‘A ROOM OF ONE’S OWN’ - Mohammadi, Ali (PEOPLE: International Journal of Social Sciences, 2021)
This inquiry investigated the major obstacles women have come across historically in producing literary works. The research scrutinised Virginia Woolf's feminist masterpiece, A Room of One’s Own. Undoubtedly. Woolf is considered as one of the precursors of 20th century feminist literary movement. During her life, she devoted herself to women's historical challenges with writing fiction. Furthermore, many of Woolf’s fiction and non-fiction productions deal with the concept of womanhood and women writers as well as their witing predicaments. The primary purpose of this study is to reflect major arguments regarding women's problems some of which are as follows: financial independence for a woman to write, social acceptance of women’s writing, historical underestimating and humiliation of female writing, the long-lasting habit of suppressing women's voice and a woman's capability as equal as a man’s to put her thoughts on the paper regardless of meaningless notions such as inferior femininity and superior masculinity. Indeed, Woolf was the first modernist-feminist writer who made women's voice heard. In addition, she attracted the public attention to the sufferings, vicissitudes and toils they have gone through over the years to be hindered from seeking equality and flourishing their writing talent. To sum up, the reason why a great number of literary masterworks have been written by men is not that women were not as gifted or accomplished as their male counterparts; rather, it is due to the fact that they have always been deprived of the required economic and material facilities and privileges men were provided. Finally, it was men who permanently defined what woman and womanhood are. Therefore, however skilful they became, they still failed to express themselves in a written way, they could not gain access to education let alone be a writer and all their abilities went unnoticed.